2010
DOI: 10.1051/medsci/2010262177
|View full text |Cite
|
Sign up to set email alerts
|

Les protéines à domaine patatine

Abstract: Identification des enzymes à domaine patatineLes lipides ont des rôles essentiels et multiples dans les cellules, que ce soit dans le maintien des structures intracellulaires et le transport vésiculaire, la régulation de l'équilibre énergétique et la génération de seconds messagers participant à des mécanismes de signalisation cellulaire. Ces dernières années, la découverte de l'ATGL (adipose triglyceride lipase) et de l'adiponutrine, deux protéines adipocytaires, a permis d'identifier une nouvelle famille d'e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Like the two ARCI‐related PNPLA1 mutations identified by Grall et al ., the mutation c.100A>G affects the patatin domain (Ile16 to Thr185; Fig. d), which features the catalytic pair Asp172 and Ser53 . It results in replacement of the hydrophobic residue alanine with hydrophilic threonine (p.Ala34Thr referred to as NP_001139189.2), a change that might well alter protein folding (Fig.…”
Section: Family 12mentioning
confidence: 87%
“…Like the two ARCI‐related PNPLA1 mutations identified by Grall et al ., the mutation c.100A>G affects the patatin domain (Ile16 to Thr185; Fig. d), which features the catalytic pair Asp172 and Ser53 . It results in replacement of the hydrophobic residue alanine with hydrophilic threonine (p.Ala34Thr referred to as NP_001139189.2), a change that might well alter protein folding (Fig.…”
Section: Family 12mentioning
confidence: 87%
“…The PNPLA family of proteins contains nine members, which play key roles in lipid metabolism 32 , 33 . While disease-causing mutations in other members of the family had been previously identified, mutations in PNPLA1 had not been previously implicated in any disease 34 37 .…”
Section: Recent Advances In Ichthyosismentioning
confidence: 99%
“…Among them, PNPLA2 is a key enzyme in the hydrolysis of stored triglycerides (TG), while PNPLA8 is a myocardial phospholipase, maintaining mitochondrial integrity [39]. The GALNT family with lipase and transacylase properties appeared to play major roles in the regulation of lipid metabolism [40]. In addition, data from Pulido et al [41] supported that RAB18 is a common mediator of lipolysis and lipogenesis, and suggested that the endoplasmic reticulum is the link that connected RAB18 action on these two processes.…”
Section: Discussionmentioning
confidence: 99%